The relative contribution of climate to changes in lesser prairie-chicken abundance - Ross, Beth E.; Haukos, David A.; Hagen, C.; Pitman, J. (My University, 2017)
Managing for species using current weather patterns fails to incorporate the uncertainty associated with future climatic conditions; without incorporating potential changes in climate into conservation strategies, management and conservation efforts may fall short or waste valuable resources. Understanding the effects of climate change on species in the Great Plains of North America is especially important, as this region is projected to experience an increased magnitude of climate change. Of particular ecological and conservation interest is the lesser prairie-chicken (Tympanuchus pallidicinctus), which was listed as "threatened" under the U.S. Endangered Species Act in May 2014. We used Bayesian hierarchical models to quantify the effects of extreme climatic events (extreme values of the Palmer Drought Severity Index [PDSI]) relative to intermediate (changes in El Nino Southern Oscillation) and long-term climate variability (changes in the Pacific Decadal Oscillation) on trends in lesser prairie-chicken abundance from 1981 to 2014. Our results indicate that lesser prairie-chicken abundance on leks responded to environmental conditions of the year previous by positively responding to wet springs (high PDSI) and negatively to years with hot, dry summers (low PDSI), but had little response to variation in the El Nino Southern Oscillation and the Pacific Decadal Oscillation. Additionally, greater variation in abundance on leks was explained by variation in site relative to broad-scale climatic indices. Consequently, lesser prairie-chicken abundance on leks in Kansas is more strongly influenced by extreme drought events during summer than other climatic conditions, which may have negative consequences for the population as drought conditions intensify throughout the Great Plains.
Citation: Ross, B. E., Haukos, D., Hagen, C., & Pitman, J. (2016). The relative contribution of climate to changes in lesser prairie-chicken abundance. Ecosphere, 7(6), 11. doi:10.1002/ecs2.1323
Keywords: Climate Change; Drought; Lesser Prairie-Chicken; Population Model; Tympanuchus Pallidicinctus; Greater Sage-Grouse